Lack of Involvement of CEP Adducts in TLR Activation and in Angiogenesis - Gounarides, John; Cobb, Jennifer S.; Zhou, Jing; Cook, Frank; Yang, Xuemei; Yin, Hong; Meredith, Erik; Rao, Chang; Huang, Qian; Xu, YongYao; Anderson, Karen; De Erkenez, Andrea; et al. (PLOS ONE, 2014)
Proteins that are post-translationally adducted with 2-(ω-carboxyethyl)pyrrole (CEP) have been proposed to play a pathogenic role in age-related macular degeneration, by inducing angiogenesis in a Toll Like Receptor 2 (TLR2)-dependent manner. We have investigated the involvement of CEP adducts in angiogenesis and TLR activation, to assess the therapeutic potential of inhibiting CEP adducts and TLR2 for ocular angiogenesis. As tool reagents, several CEP-adducted proteins and peptides were synthetically generated by published methodology and adduction was confirmed by NMR and LC-MS/MS analyses. Structural studies showed significant changes in secondary structure in CEP-adducted proteins but not the untreated proteins. Similar structural changes were also observed in the treated unadducted proteins, which were treated by the same adduction method except for one critical step required to form the CEP group. Thus some structural changes were unrelated to CEP groups and were artificially induced by the synthesis method. In biological studies, the CEP-adducted proteins and peptides failed to activate TLR2 in cell-based assays and in an in vivo TLR2-mediated retinal leukocyte infiltration model. Neither CEP adducts nor TLR agonists were able to induce angiogenesis in a tube formation assay. In vivo, treatment of animals with CEP-adducted protein had no effect on laser-induced choroidal neovascularization. Furthermore, in vivo inactivation of TLR2 by deficiency in Myeloid Differentiation factor 88 (Myd88) had no effect on abrasion-induced corneal neovascularization. Thus the CEP-TLR2 axis, which is implicated in other wound angiogenesis models, does not appear to play a pathological role in a corneal wound angiogenesis model. Collectively, our data do not support the mechanism of action of CEP adducts in TLR2-mediated angiogenesis proposed by others.